A Review and Scientometric Analysis of Global Research on Prefabricated Buildings - Wenhui Liu; Hong Zhang; Qian Wang; Tianran Hua; Hong Xue (Advances in Civil Engineering)
Prefabricated building has become one of the most significant research directions in the architecture, engineering, and construction (AEC) industry and has attracted a large number of scholars and practitioners in recent years. However, few studies have conducted a systematic review on the development of prefabricated building research around the world. In this study, the scientometric method is used to analyze the literature on prefabricated buildings in the past ten years through analysis of co-authors, co-words, and co-citation. From the Web of Science (WOS) core collection database, a total of 1224 articles were collected for statistics and analysis. The analysis results indicated that Bruno Dal Lago obtained the maximum number of co-citations, and the most significant country/region and research institution in prefabricated building research were China and Tongji University, respectively. It was also found that engineering, civil engineering, and construction and building technology were the top three subject categories that prefabricated building research belonged to. Among all the keywords of the collected articles, citation bursts were received by “cladding panel,” “precast concrete,” and “project.” Moreover, there were 11 co-citation clusters identified from the articles, and their themes included precast structures, waste management, progressive collapse, delay, precast facades, carbon reduction, laser scanning, and prefabricated residential building. This paper is expected to provide researchers and practitioners in this field a detailed and in-depth understanding of the trend and status of global research on prefabricated buildings.